Validity and feasibility of the self-report EQ-5D-Y as a generic Health-Related Quality of Life outcome measure in children and adolescents with Juvenile Idiopathic Arthritis in Western Cape, South Africa - Desiree Scott; Christiaan Scott; Jennifer Jelsma; Deepthi Abraham; Janine Verstraete (AOSIS, 2019)
Background: Health-Related Quality of Life (HRQoL) data together with clinical findings allow for monitoring of intervention efficacy and the effect on HRQoL. Children with Juvenile Idiopathic Arthritis (JIA) experience symptoms often persisting into adulthood, emphasising the need to track HRQoL. Objectives: The aim of this study was to investigate psychometric properties of the EuroQol five-dimensional youth questionnaire (EQ-5D-Y) in children with JIA. Methods: A cross-sectional, analytical study design was used. Children 8 to 15 years were recruited, completing the self-report EQ-5D-Y and two other HRQoL questionnaires. Known group validity was established by comparing the effect size between children with different disease severities. Concurrent validity was tested using Kruskal-Wallis to compare the ranking of scores on different questionnaires. Feasibility was assessed by number of missing responses and time to complete each questionnaire. Results: All questionnaires were able to distinguish between children with different JIA severity. There was a significant difference in ranking of most Juvenile Arthritis Multidimensional Assessment Report dimension scores across EQ-5D-Y levels, (p < 0.05), indicating concurrent validity. There was poor concurrent validity with the PedsQL dimensions tested with EQ-5D-Y, except for 'pain' (p = 0.001). The EQ-5D-Y was the quickest to complete with no missing values. Conclusion: This study showed that the EQ-5D-Y is valid and feasible in measuring HRQoL in JIA children and adequately responsive to detect change over time. Clinical implications: It is quick and easy to use in a busy clinical setting, allowing for effective JIA management monitoring.